Self-destructive content in university teaching: new challenge in the Digital Competence of Educators (Communication & Society, 2020)
The Z are the first digital native people gaining access to university. It is a generation that registers high rates of social media consumption, but their digital competence is not as outstanding as one might expect due to the training’ deficiency they have acquired in previous educational levels caused, among other reasons, by the primary and secondary teachers’ low digital competence. The current research aims to identify the demand for using social networks and messaging apps 2.0 in university teaching. A quantitative methodology was employed in order to know the technological prospects of the university Z in the Euroregion Galicia-North of Portugal, in the context of an Erasmus mobility. The results confirm the necessity to continue using social media, but only those within the students’ technological comfort zone; thus, it is necessary to combine transmedia storytelling with the insertion of technological proposals in environments initially not conceived for learning. It is concluded that the Z are starting to claim the use of state-of-the-art resources such as self-destructive content, which requires an immediate improvement in the university educators’ digital competence by means of continuing training programmes, since only the pioneer educators with a C2 level can detect and pay attention to this type of demands.